The News Framing Analysis Of Vina's Murder Case On Tvonenews.Com - Alya Mutia Dewi; Yuliati Yuliati; Nurlianti Muzni (Green Publisher Indonesia, 2024)
This research analyzes the news framing of the Vina murder case in tvOnenews.com media using a qualitative method with a descriptive approach through Robert N. Entman's framing analysis model, which divides framing into four categories: problem definition, cause diagnosis, moral judgment, and resolution recommendations. The results showed that tvOnenews.com framed this case as a symbol of the weakness of the Indonesian legal system, with an emphasis on justice and openness in the legal process. The media also highlighted the efforts of the victim's family in seeking justice, and debated various factors causing injustice in this case, including the alleged involvement of unscrupulous people and the possibility of false testimony. This research emphasizes that through intense news framing, tvOnenews.com has attempted to be an agent of social change that encourages the creation of justice and improvement of the legal system in Indonesia. This research provides insight into how the media can frame legal issues to build public opinion and influence people's perceptions.